If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8d + 2d + -3d + 4 = 6d Reorder the terms: 4 + 8d + 2d + -3d = 6d Combine like terms: 8d + 2d = 10d 4 + 10d + -3d = 6d Combine like terms: 10d + -3d = 7d 4 + 7d = 6d Solving 4 + 7d = 6d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-6d' to each side of the equation. 4 + 7d + -6d = 6d + -6d Combine like terms: 7d + -6d = 1d 4 + 1d = 6d + -6d Combine like terms: 6d + -6d = 0 4 + 1d = 0 Add '-4' to each side of the equation. 4 + -4 + 1d = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 1d = 0 + -4 1d = 0 + -4 Combine like terms: 0 + -4 = -4 1d = -4 Divide each side by '1'. d = -4 Simplifying d = -4
| 2x-17=19+5x | | 3y/4-y/2=10 | | ln(y-b)=5t | | -x-18=10-3x | | -27-5x=-7x+9 | | -1-9=8x+6-7x | | -7p+2=107 | | 57+6x=-218-5x | | 4v^2-3v-19=0 | | -1.6+2x^2=180 | | 8x-6x+192=8x+84 | | lny=-t+5 | | 8x-29=11x+55 | | 1-5x-3x=17 | | 21z-35=20x-45 | | a/2+7=1 | | 8d+12-b=8+7b+4 | | -29-11x=-7x+31 | | 1-2+(-12)= | | 3(5x+3)-25=12x+2 | | 2a+3b+6c=54 | | 17+4x=61 | | 4(2-y)=y-7 | | 14+8x=-24+6x | | 5x+3(4x-10)=180 | | (5x^2)-7x-1=0 | | A-2b-4c=D | | x(x+3)-4=3x+32 | | 9x-4x^2=0 | | x+x(0.13)=1300 | | -2(n+1)=1-2n | | 7x+4x-16=64-5x |